Combatting Bacterial Pathogens with Immunomodulation and Infection Tolerance Strategies - M. Fura, Jonathan; Sarkar, Sourav; E. Pidgeon, Sean; M. Pires, Marcos (Current Topics in Medicinal Chemistry, 2017)
The discovery of antibiotics is one of the most significant milestones in modern medicine. Upon the advent of the antibiotic era, invasive surgical procedures, which were previously deemed too risky because of the possibility of bacterial infection, became a reality. In the process, medicine as a whole made great strides that led to the rise of the average human life span by almost three decades. Unfortunately, over the course of time bacteria have started to evolve resistance to antibiotic agents being administered, thus rendering many of these drugs ineffective (or on the verge of being ineffective). Today, the number of antibiotic-resistant bacteria continues to escalate and yet the number of new antibiotics being approved for clinical use has drastically decreased. The combination of these two factors has brought about a primary public health crisis for the 21st century. In order to maintain the status quo of modern medicine, new antibiotics need to be discovered and developed. Two emerging new strategies that hold considerable promise is the use of immunomodulator antibiotics and infection tolerance agents. Rather than targeting the bacteria directly, as traditional antibiotics do, these agents function to clear or tolerate infections by interfering with the bacterial colonization process and by stimulating the immune system of infected host. This review focuses on the different types of immunomodulation antibiotics and infection tolerance strategies that have been discovered over the last two decades and the mechanisms by which they act upon the host system to effectively combat bacterial infections.
Keywords: Infection